GAMBARAN FAKTOR RISIKO KEJADIAN BAYI BERAT LAHIR RENDAH (BBLR) DI RSUD dr. R. GOETENG TAROENADIBRATA PURBALINGGA TAHUN 2013 - Ema Wahyuningrum; Etika Ervanti (Viva Medika, 2014)
Infant Low Birth Weight (LBW) is a newborn whose weight at birth of less than 2500 grams (upto 2499 grams). The cause of LBW in general because of several factors, including maternalfactors such as disease (anemia, bleeding, IMS, premature rupture of membranes, preeklampsiand eclampsia), age, parity, socioeconomic circumstances. Fetal factors such as infection of thefetus and multiple pregnancies, as well as environmental factors. In dr. R. GoetengTaroenadibrata Purbalingga, LBW in 2013 as many as 237 cases (19.47%).The study aims todescribe risk factors of low birth weight (LBW) by maternal factors in dr. R. GoetengTaroenadibrata Purbalingga 2013. This research is descriptive quantitative research with crosssectional study with retrospective time approach. Sampling in this study using total sampling,sample of this research is all infants with low birth weight based medical record dr. R. GoetengTaroenadibrata Purbalingga the year 2013 as many as 237 cases. Measuring instruments usedmaster table and type of data is secondary data. Data were analyzed using univariate. The resultshowed a risk factor for low birth weight by the age of majority is 20-35 years as many as 101respondents (65.3%), based on the parity mostly primiparas total of 133 respondents (56.1%)and by disease or pregnancy complications mostly experienced respondent is preeclampsia were92 respondents (38.8%). Risk factors of low birth weight (LBW) in dr. R. GoetengTaroenadibrata Purbalingga in 2013, mostly aged 20-35, primiparous parity and have a historyof preeclampsia. Keywords: risk factors, Infant Low Birth Weight (LBW)